The Sex Differences in Regulating Unpleasant Emotion by Expressive Suppression: Extraversion Matters - Cai, Ayan; Lou, Yixue; Long, Quanshan; Yuan, Jiajin (Frontiers in Psychology, 2016)
Males are known for more suppression of emotional displays than females. However, when the emotion regulation effect of expressive suppression is greater in males, and how this sex difference varies with emotion display-related personality (e.g. extraversion), are undetermined. Event-related potentials were recorded while male and female participants different in extraversion were required to attend or suppress emotional expression, to negative pictures. Sex and extraversion did not modulate self-reported emotional experience. However, Late Positive Potential (LPP) amplitudes showed an extraversion-moderated sex difference in the 2000-3000ms and the 3000-4000ms time epochs. LPP amplitudes were decreased during suppression versus viewing condition in ambivert males, while this effect was absent in ambivert females. However, the LPP amplitudes of extraverts were similar for suppression and viewing conditions, irrespective of sex and timing. Regardless of early, middle or late time window, LPP amplitudes were positively related to self-reported emotion. These results suggest a male advantage using expressive suppression for emotion regulation in non-extraverted, ambivert individuals.